Intelligent lesion blood-brain barrier targeting nano-missiles for Alzheimer's disease treatment by anti-neuroinflammation and neuroprotection - Xueqin He; Xiaorong Wang; Lianyi Yang; Zhihang Yang; Wenqi Yu; Yazhen Wang; Rui Liu; Meiwan Chen; Huile Gao (Elsevier, 2022)
The treatment of Alzheimer's disease (AD) is one of the most difficult challenges in neurodegenerative diseases due to the insufficient blood‒brain barrier (BBB) permeability and unsatisfactory intra-brain distribution of drugs. Therefore, we established an ibuprofen and FK506 encapsulated drug co-delivery system (Ibu&FK@RNPs), which can target the receptor of advanced glycation endproducts (RAGE) and response to the high level of reactive oxygen species (ROS) in AD. RAGE is highly and specifically expressed on the lesion neurovascular unit of AD, this property helps to improve targeting specificity of the system and reduce unselective distribution in normal brain. Meanwhile, these two drugs can be specifically released in astrocytes of AD lesion in response to high levels of ROS. As a result, the cognition of AD mice was significantly improved and the quantity of Aβ plaques was decreased. Neurotoxicity was also alleviated with structural regeneration and functional recovery of neurons. Besides, the neuroinflammation dominated by NF-κB pathway was significantly inhibited with decreased NF-κB and IL-1β in the brain. Overall, Ibu&FK@RNPs can efficiently and successively target diseased BBB and astrocytes in AD lesion. Thus it significantly enhances intracephalic accumulation of drugs and efficiently treats AD by anti-neuroinflammation and neuroprotection.